KAJIAN EKSISTENSI PASAR TRADISIONAL KOTA SURAKARTA - Maritfa Nika Andriani; Mohammad Mukti Ali (Jurusan Perencanaan Wilayah dan Kota, 2013)
Surakarta city covers five districts inhabited by about 588,110 people and as a center of growth by population more than 500 thousand people in the hinterland region so that be the target of the modern market as it has tremendous market share. The development of modern markets was increasing in Surakarta both located in the city center and located in rural areas and the border with the surrounding area. It makes traditional markets become marginalized. In fact, hundreds to thousands of lives traders rely on traditional markets. Traditional markets are spearheading of community economy so that it needs to get serious attention in order to remain in existence or even can increase their existence so as to support the welfare of trader. Therefore, it appears research question “How does the existence of the traditional market town of Surakarta?” The research objects are Legi market and Mojosongo market of Surakarta city. While the limits of the existence that referred to in this study is the existence of traditional market that have an survive element which recognized by others as the sustainability activities of the traditional market itself that experiencing growth, stagnation, or even decline depends on the ability to actualize its potential. The purpose of this study was to determine the existence condition of Legi Markets and Mojosongo Market, what it is experiencing growth, stagnation or decline? What the attempt can be done to maintain the existence of both the traditional markets? In assessing the existence of the traditional market of Surakarta city are analyzed three targets included: analysis of traditional markets existences, determine the condition of traditional markets existences based on the characteristics of market, traders and visitors perceptions of market to traditional market existences. After knowing the condition of their existence then next analysis is what the attempt can be done to maintain the existence of traditional markets through two analyzes include analysis of government policies related to traditional markets and analysis of social capital as an effort of traders to maintain the existence of the traditional market. Research approach with mixed method is a method that combines quantitative methods and qualitative methods by using qualitative methods is more dominant than quantitative methods. The techniques of primary data collection were performed by field observations, questionnaires to traders and visitors of the market, and interview the parties involved. Secondary data was obtained from a literature review and survey the agencies. From the stages of the analysis carried out can be concluded that the existence of Mojosongo market is in a stagnation existence condition, while the existence of Legi market is in decline existence conditions. The efforts to maintain the existence of both the traditional markets are with regulatory policy and development of market infrastructure as well as maintain the social capital consists of norms, beliefs, and bargaining as an effort of traders to maintain the existence of traditional markets. One of the recommendations given is to provide and improve facilities and infrastructure of markets both located in the market and in the market Legi Mojosongo so that visitors feel comfortable when shopping and are reluctant to switch to other markets which the market infrastructure is better than that found in both the traditional markets, and in order to maintain the social capital consists of the norms, beliefs, and bargaining where social capital can maintain a relationship of buyers trust and increase loyalty buyers to keep coming back to shop at traditional markets.